(untitled) (Medical Forum Monthly, 2024)
Objective: Psoriasis is a chronic inflammatory skin disease of unknown origin. Different factors might be influencing its course. The aim of our study was to observe and analyze different clinoepidemiological variables of psoriasis in patients reporting to a tertiary care hospital in Karachi. Study Design: Prospective study Place and Duration of Study: This study was conducted at Jinnah Postgraduate Medical Centre, Karachi, Pakistan from January 2014 to December 2014. Materials and Methods: 200 patients (116 Males and 84 females) ages 18 and above with mild to severe psoriasis were selected and assessed on one occasion which included detailed history and examination. All data was documented on completion of study. Results: A total 200 cases were studied. 90% had chronic plaque psoriasis. There was male preponderance with a male to female ratio of 1.38:1. Mean peak age of onset was 11-20 years of age and was earlier in females than males. More than two-third of patients had onset of psoriasis before or at 40 years of age. Familial occurrence was present in 38% of patients and 35% had first degree relative involvement. Psoriatic arthropathy was present in 35% of patients. 86.36% of the patients with arthropathy had onset of psoriasis before 40 years of age. 21% of patients reported worsening of their psoriasis with sun. 32% of the patients in this study were smokers and most of them were males. Conclusion: The findings of this study done in Karachi, Pakistan correlates with previous hospital-based studies done in different parts of the world.